Sustainable textiles repel biting bugs.
Chemical resistance in insects and other arthropods, as well as stricter legislation of the pesticide market and anthropogenic factors, such as climate change, all demand new technologies for controlling ticks and bedbugs. An EU-funded consortium is therefore developing textile technologies to protect European citizens from attack.